1989
DOI: 10.2337/diab.38.9.1123
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation of Adipocytes and Endothelial Cells Required for Catecholamine Stimulation of PGI2 Production by Rat Adipose Tissue

Abstract: Disturbances of prostaglandin I2 (PGI2, prostacyclin) production by adipose tissue contribute to the pathogenesis of diabetic ketoacidosis and may contribute to the pathogenesis of hypertension and vascular disease. We studied the cellular basis of PGI2 production in adipose tissue, measured as release of 6-keto-PGF1 alpha in response to epinephrine. Adipocytes did not produce PGI2 when nonfat cells were removed by repeated washing. The nonadipocyte cellular constituents of adipose tissue (nonfat cells) did no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1991
1991
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…In fact, it can be the largest organ in the body. This is physiologically and pathophysiologically important because the total amount of secreted adipokines are enormous and may affect the whole body economy, especially considering that every adipocyte is connected to the vascular network [69]. It is well known that dysregulation of the production and secretion of adipokines is involved in the development of metabolic and cardiovascular diseases.…”
Section: Role Of Adipokinesmentioning
confidence: 99%
See 2 more Smart Citations
“…In fact, it can be the largest organ in the body. This is physiologically and pathophysiologically important because the total amount of secreted adipokines are enormous and may affect the whole body economy, especially considering that every adipocyte is connected to the vascular network [69]. It is well known that dysregulation of the production and secretion of adipokines is involved in the development of metabolic and cardiovascular diseases.…”
Section: Role Of Adipokinesmentioning
confidence: 99%
“…Antilipolytic stimuli, insulin, for example, reduce the release of prostaglandins [100] such as prostacyclin (PGI 2 ). On the basis that insulin decreases the production of this strong vasodilator, Parker and coworkers suggested that hypertension associated with insulin resistance and hyperinsulinemia (i.e., metabolic syndrome) would be due partly caused by the lack of proper PGI 2 release [69]. It appears that PGI 2 production by the adipocytes results from the cooperation of adipocytes and vascular endothelial cells.…”
Section: Role Of Adipokinesmentioning
confidence: 99%
See 1 more Smart Citation
“…In AT, prostaglandin I2 (PGI 2 ) and E2 (PGE 2 ) are the two most abundant members of the family present ( 188 ). Studies have proposed the importance of the presence of both non-fat cells, predominantly endothelial cells, and adipocytes for optimal AT prostaglandin production and secretion ( 189 , 190 ). Experiments using isolated endothelial cells from human adipose capillaries presented evidences that human AT endothelial cells are capable to secrete both PGI 2 and PGE 2 ( 191 ).…”
Section: Small Moleculesmentioning
confidence: 99%
“…The advent of the always overlooked PVAT, turned over the whole concept into an inward signaling. It is worth to remember that an interaction of endothelial cells and adipocytes was proposed in the late eighties, before PVAT was known as such (Parker et al, 1989) and Richelsen published a review supporting the concept that adipocytes provide the endothelial cell with arachidonic acid for the synthesis of prostaglandins and that the release of these substances requires the action of both kind of cells (Richelsen, 1992). Since these initial proposals our understanding of the cross-talk between the different cells of the vascular milieu has experimented a remarkable growth.…”
Section: New Pathways In the Regulation Of Vascular Motionmentioning
confidence: 99%